MASJID NABAWI SEBAGAI DASAR PEMBENTUKAN MASJID AGUNG KRATON SURAKARTA - Hermanto, Heri; Hidayah, Atinia (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
ABSTRACT Prophet Muhammad was the architect and ground-breaking stone for the construction of the Prophet's Mosque or an-Nabawi in Medina in 622. The Prophet's Mosque was established with a very simple design yet it owns beneficial functions. The Prophet's Mosque is a place often used for various purposes for instance as government centers, learning centers, medical treatment place, detention and rehabilitation centers, and certainly more social or worshipping center. Building designed with a simple form but rich in functions had never existed before. Therefore, Prophet's Mosque had become the basis, inspiration, and catalyst for the development of Islamic civilization especially mosque architecture. The architecture of the mosque then became the most important identity for the progress of Muslims. The essence of Muslim architecture lies in function with all of its dimensions including the physical, intellectual, and spiritual aspects. The role of form is also important, but only insofar as it complements and enhances function. There are four typical mosques that are considered to represent the heritage of Islamic architecture in this world which were inspired by the Prophet's Mosque, namely; Arabic Type, Turkish Type, Persian Type, and Indian Type. This typology does not include the type of Indonesian mosque, even though the mosques built by Walisongo and the kings of Islamic Mataram in Java are no less great and unique compared to other famous mosques in the world. The question that then emerges is whether or not the Prophet's Mosque is the basis and inspiration for the realization of the Architecture of the Great Mosque of Keraton Surakarta.